Management accounting practices in 2.0 Malaysian Public Universities / Corina Joseph - Joseph, Corina (Institut Teknologi Mara Cawangan Sarawak, 2003)
This study reports on a survey of management accounting practices in public universities in Malaysia. It aims to identify the management accounting an : practices adopted in the Malaysian public universities and is conducted using the way questionnaire survey method. This study also attempts to investigate the conti relationship between the problems in applying management accounting techniques and the nature of the management accounting techniques as well as 2.2 the characteristics of the practitioners themselves. The reports of this study have revealed that the management accounting practice is generally applied in the universities.